2021
DOI: 10.1016/j.heliyon.2021.e07091
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, molecular, and virulence characterization of entomopathogenic fungi, Beauveria bassiana (Balsam) Vuillemin, and Metarhizium anisopliae (Metschn.) Sorokin from soil samples of Ethiopia for the development of mycoinsecticide

Abstract: Fungal entomopathogens are the most effective biocontrol agents against insect pests in the natural ecosystem. This study was conducted for phenotypic, molecular, and virulence characterization of locally isolated entomopathogenic fungi from soil samples of six localities in Ethiopia. Entomopathogenic fungi were isolated from 120 soil samples with the galleria baiting method. A total of 65 (54.2%) entomopathogenic fungal isolates belongs to Beauveria spp and Metarhizium spp were identified based on cultural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
3
25
0
3
Order By: Relevance
“…2021) characterized the EPF morphologically indicating the presence of white or yellowish white colony, globose or sub-globose conidia were essential for the confirmation of B. bassiana. In the present study, the isolated EPF isolates produced whitish and yellowish white colony, globose and sub-globose conidia were in accordance with the findings of (Gebremariam et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…2021) characterized the EPF morphologically indicating the presence of white or yellowish white colony, globose or sub-globose conidia were essential for the confirmation of B. bassiana. In the present study, the isolated EPF isolates produced whitish and yellowish white colony, globose and sub-globose conidia were in accordance with the findings of (Gebremariam et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Isolates were obtained from soil samples collected from farmlands and forest sites of Ethiopia. The potential isolates were selected based on their virulence effectiveness [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The keystone genus of the bacterial community in the OMF group was Pseudomonas , and the keystone genus of the fungal community was Metarhizium ( Supplementary Table S3 ), both of which are recognized as biocontrol microorganisms. Pseudomonas can adsorb heavy metals in soil and promote plant growth ( Costa-Gutierrez et al, 2020 ; Ghorbanzadeh et al, 2020 ; Wu et al, 2022 ), whereas Metarhizium can kill plant pests and mitigate plant diseases ( Riguetti Zanardo Botelho et al, 2019 ; Gebremariam et al, 2021 ; González-Pérez et al, 2022 ). In conclusion, this study demonstrated that the application of organic fertilizer, especially OMF, can not only enhance the connectivity, cohesiveness and stability of microbial community network structure, but also increase the abundance of beneficial microorganisms.…”
Section: Discussionmentioning
confidence: 99%